Integrated Electronic Medical Record Design With Nutritional Screening System at NCC’s Teaching Factory - Deharja, Atma; Yunus, Muhammad; Suryana, Arinda Lironika (International Journal of Health and Information System, 2024)
One of Politeknik Negeri Jember's Teaching Factories (TEFA) that offers community nutrition services is the Nutrition Care Centre (NCC). The design of electronic medical records (EMRs) for continuous care patients, especially those with non-communicable diseases, is being studied in order to meet the ever-increasing needs of health care, assist patients who require continuous care, and improve the way that modern medical technology serves humans. The Waterfall framework concept is used in the research process, and an electronic medical record system is designed in accordance with the goals and the overall architecture of the system. Black-box testing and white-box testing are then conducted to evaluate the features, dependability, and stability of the designed electronic medical record system. Furthermore, when combined with other research findings, the design's viability is demonstrated. It is evident that the electronic medical record system created for the study's patients who require ongoing care is entirely workable. As electronic medical records continue to develop, there will be more opportunities to research and enhance this system, which will benefit patients and hospitals alike in the long run.